Fine roots in young Eucalyptus dunnii Maiden trees - Dick, Grasiele; Schumacher, Mauro Valdir (Revista Ecologia e Nutrição Florestal - ENFLO, 2019)
The fine roots provide the eucalyptus cultivation in the most diverse soil conditions, contributing to the cycling of nutrients and improvement of soil fertility. The present study aimed to characterize the biomass production and distribution of fine roots (≤ 2 mm) in young Eucalyptus dunnii Maiden trees, cultivated in Pampa biome, Rio Grande do Sul state. Sixteen months after planting nine monoliths, divided in 0 to 5, 5 to 10, 10 to 15 and 15 to 20 cm of soil depth were collected. The total production of fine roots is 727.4 kg ha-1 and, root biomass does not differ between the depths of the soil. The density of the fine roots varies from 0.31 to 0.39 g dm-3, subtly reducing after 15 cm of the soil profile. This homogeneous root distribution indicates that mineral fertilization can be incorporated in up to 20 cm of soil depth and, in the short term, through turnover, these fine roots will be decomposed and added to the organic matter, providing improvements in soil fertility.